Analisis Pengaruh Kualitas Pelayanan dan Biaya terhadap Kepuasan Peserta Kursus pada LKP Lestari Komputer - Sri Lestari; Fahrudin Fahrudin; Toto Sudibyo; Nurkhayati Nurkhayati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the effect of service quality and cost on course participants’ satisfaction at LKP Lestari Komputer. The research employs a quantitative approach using a survey method through questionnaires distributed to 50 active course participants from September to October 2025. The independent variables consist of service quality (X₁) and cost (X₂), while the dependent variable is participants’ satisfaction (Y). Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The regression equation obtained is Y = -4.572 + 0.742X₁ + 0.287X₂. The t-test results show that service quality (t = 5.221; sig = 0.000) and cost (t = 2.538; sig = 0.015) have a positive and significant effect on participants’ satisfaction. The F-test result shows an F value of 49.180 with a significance level of 0.000, indicating that service quality and cost simultaneously have a significant effect on participants’ satisfaction. The coefficient of determination (R²) of 0.672 indicates that 67.2% of the variation in participants’ satisfaction is explained by both variables.